2005
DOI: 10.3341/kjo.2005.19.3.161
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Lower Lid Retraction Combined with Entropion using an Ear Cartilage Graft in the Anophthalmic Socket

Abstract: Purpose: To investigate the surgical results of an ear cartilage graft and supplemental procedures for correcting lower lid retraction combined with entropion in anophthalmic patients. Methods: We reviewed retrospectively the medical records of 7 anophthalmic patients with lower lid retraction and entropion, who received a posterior lamellar ear cartilage graft and one or both of lateral tarsal strip or eyelash-everting procedure between March 1998 and March 2003. Preoperative and postoperative lid and socket … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…13,14 Conchal cartilage is relatively abundant and it is not as invasive to harvest as other donor sites. The natural curve of the conchal cartilage makes it a good match for the convexity of the eyelid.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Conchal cartilage is relatively abundant and it is not as invasive to harvest as other donor sites. The natural curve of the conchal cartilage makes it a good match for the convexity of the eyelid.…”
Section: Discussionmentioning
confidence: 99%
“…Although keratinization can occur, it only irritates the ocular surface [9,12,13]. As an alternative material, auricular cartilage is sometimes used via a transconjunctival approach, and some of this cartilage remains exposed and requires removal [9,14,15]. In many cases, the transconjunctival approach for lengthening of the posterior lamella, is not suitable for maintaining.…”
Section: Discussionmentioning
confidence: 99%
“…All patients had satisfactory functional and cosmetic results. More recently, Moon et al 33 reported their results of ear cartilage grafting to correct lower eyelid retraction combined with entropion in 7 anophthalmic sockets. In their study, eyelid retraction was corrected with no recurrences during follow-up, but entropion of the lower eyelid recurred in 4 patients.…”
mentioning
confidence: 97%